Purinergic P2X7 receptor mediates hyperoxia-induced injury in pulmonary microvascular endothelial cells via NLRP3-mediated pyroptotic pathway - Zeng Wen; Deng Zhuyu; Li Huaying; Gao Shuqiang; Ju Rong (Open Medicine)
Hyperoxia-induced injury is a well-recognized cause of bronchopulmonary dysplasia (BPD). Existing research studies have not well elucidated the exact mechanisms underlying hyperoxia-induced cellular damage. This study examines the involvement of the P2X7 receptor (P2X7R) in hyperoxia-induced damage to human pulmonary microvascular endothelial cells (HPMVECs) via the NOD-like receptor family, pyrin domain-containing protein 3 (NLRP3) pathway.